KONSEP AYAH SEBAGAI PENDIDIK ANAK REMAJA DALAM PERSPEKTIF Q.S. YUSUF: 17-18 - Farouq, Umar; Andriana, Nesia; Sadriahati, Tating (Darul Hikmah: Jurnal Penelitian Tafsir dan Hadits, 2021)
The emergence of moral decadence and mental weakness in adolescents in society generally begins with poor family education and parenting. The role of fathers as educators is very strategic to create a generation of teenagers who have a straight faith, have good morals, have a tough spirit and have a strong body. This is because the first and foremost education for children is the family environment. Studies to optimize the role of fathers need to be done. This study aims to analyze the concept of fathers as educators of adolescent children based on Q.S. Joseph: 17-18. The method used in this research is a qualitative method with a literature study approach. This study leads to a conclusion in the form of the concept of fathers as educators of adolescent children. This concept includes aspects of the function, method and ideal character of the father. The function aspect consists of two, namely the existence function which includes functions as a leader, supervisor and protector. The function of educators includes educators of faith, morals, spiritual and physical. Optimizing the function of faith education is supported by elements of instilling faith and monotheism. The function of moral educators is supported by the cultivation of honesty, firmness and courage to sacrifice, responsibility and trust. Spiritual functions are supported by the process of growing patience, gratitude and mahabbah. Physical function can be realized by playing activities, sports or competitions. The ideal method of a father in educating teenagers includes exemplary methods, advice, effective communication, rewards and punishments. Meanwhile, the ideal character that a father must possess includes faith and piety, knowledge and fairness, patience, forgiveness, tawakkal and lots of prayer.